POTENTIAL DISTRIBUTION ZONES FOR SOYBEAN RUST (Phakopsora pachyrhizi) IN MEXICO - Yañez-Lopez, Ricardo; Hernández-Zul, María Irene; Quijano-Carranza, Juan Ángel; Terán-Vargas, Antonio Palemón; Pérez-Moreno, Luis; Díaz-Padilla, Gabriel; Rico-García, Enrique (Ecosistemas y Recursos Agropecuarios, 2015)
Asian Soybean Rust is one of the most important soybean diseases. Since the past decade, some im- portant soybean production areas in America, like Brazil and the United States of America, have been affected by this disease. Due to the seriousness of this threaten, in 2009, the Mexican government implemented a surveillance program based on the installation and monitoring of sentinel plots in areas planted with crops considered as susceptible hosts for this organism. In order to support the strategy to prevent the establishment of the disease in Mexico, in the present study the potential distribution of the organism was evaluated considering the following criteria: 1) the suitability of climatic conditions for soybean rust; 2) the extent of the cultivated areas with susceptible hosts, and 3) the inoculums availability. Favorable days for Asian soybean rust infection were calculated with a simple model which uses climatic variables as inputs. The model was applied to classify the agricultural areas of the country according to the probability of occurrence of favorable conditions for infection of soybean rust in the summer and winter growing seasons. The Results indicate that in the summer the greatest number of favorable days for infection occurs, mainly in Tamaulipas, Veracruz, Yucatan, Chiapas, Oaxaca, Guerrero, Michoacan, Jalisco, Nayarit, Sinaloa and Sonora. In the winter, the favorable days decrease considerably. Based on these results we conclude that the probability that the Asian soybean rust would be overwintering in Mexico is low.